Community-Based Malaria Testing Reduces Polypharmacy in a Population-Based Survey of Febrile Illness in Western Kenya - Jeremiah Laktabai; Jeremiah Laktabai; Alyssa C. Platt; Elizabeth Turner; Elizabeth Turner; Indrani Saran; Joseph Kipkoech; Diana Menya; Wendy Prudhomme O'Meara (Frontiers Media S.A., 2022)
Objective: The objective was to describe the relationship between the location of care, the malaria test result, and the type of medicine consumed for the fever, and to determine whether community-based access to malaria testing reduced polypharmacy.Methods: This is a secondary analysis of a cluster-randomized trial of an intervention designed to increase diagnostic testing and targeting of Artemesinin Combined Therapies (ACTs). Data collected at baseline, 12, and 18 months were analyzed to determine the impact of diagnostic testing on drug consumption patterns among febrile individuals.Results: Of the 5,756 participants analyzed, 60.1% were female, 42% were aged 5-17 years, and 58.1% sought care for fever in a retail outlet. Consumption of both ACT and antibiotics was 22.1% (n = 443/2008) at baseline. At endline, dual consumption had declined to 16.6%. There was reduced antibiotic consumption among those testing positive for malaria (39.5%-26.5%) and those testing negative (63.4%-55.1%), accompanied by a substantial decline in ACT use among malaria-negative participants.Conclusion: Diagnostic testing for malaria reduces dual consumption of ACTs and antibiotics, especially among those testing outside the formal healthcare sector.